2001
DOI: 10.1002/1521-3951(200107)226:1<57::aid-pssb57>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Alternative Gate Dielectrics: A Theoretical Approach

Abstract: We describe several applications of first-principles computational methods based on density functional theory (DFT) to the study of potential gate dielectric materials. First we investigate the stability of binary alkaline earth oxides in contact with Si and SiO 2 . In particular, we consider the case of SrO, which is important for the epitaxial growth of the SrTiO 3 perovskite structure on the Si (001) surface. Then we discuss the energetics of the SrTiO 3 (001) surface. We conclude with a brief discussion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(53 citation statements)
references
References 28 publications
6
46
0
Order By: Relevance
“…separated by an energy gap of 3.8 eV from a conduction band composed of Hf 5d character. This is in agreement with previous theoretical studies [33][34][35] as well as with the photoemission and inverse photoemission data obtained from HfO 2 deposited on SiO x N y / pSi, which showed that the valence band mainly consists of O 2p nonbonding orbitals of symmetry while the conduction band is primarily Hf 5d-like nonbonding orbitals. 35 However, our calculations show that the upper valence band exhibits mixing of the O 2p and Hf 5d states, indicating covalency of the Hf-O bonds.…”
Section: Electronic Structuresupporting
confidence: 93%
“…separated by an energy gap of 3.8 eV from a conduction band composed of Hf 5d character. This is in agreement with previous theoretical studies [33][34][35] as well as with the photoemission and inverse photoemission data obtained from HfO 2 deposited on SiO x N y / pSi, which showed that the valence band mainly consists of O 2p nonbonding orbitals of symmetry while the conduction band is primarily Hf 5d-like nonbonding orbitals. 35 However, our calculations show that the upper valence band exhibits mixing of the O 2p and Hf 5d states, indicating covalency of the Hf-O bonds.…”
Section: Electronic Structuresupporting
confidence: 93%
“…Our results are also in good agreement with previous DFT calculations of this material. 35 Note however, that the experimental data for cubic and tetragonal phases are taken at high temperature, e.g., 2073 K for tetragonal, and are also somewhat dependent on temperature, and therefore comparisons with the 0 K theoretical data are limited. The electron density of states ͑DOS͒ for ideal monoclinic hafnia is shown in Fig.…”
Section: A Ideal Crystalsmentioning
confidence: 99%
“…Vibrational spectroscopy studies and theoretical work on zirconia have been performed, 1,[12][13][14][15] and other studies were focused on phase transitions under pressure.…”
mentioning
confidence: 99%